An Emperical Study on India’s Foreign Trade and Policy: Impact of India's trade and external sector on GDP growth and per capita income (Journal of Advances and Scholarly Researches in Allied Education, 2022)
India's nominal gross domestic product (GDP) at current prices is estimated at Rs. 232.2 trillion(US 3.1 trillion) in 2021-22. India's trade and external sector had a significant impact on the GDP growthand expansion in per capita income. India's overall exports (Merchandise and Services combined) inApril-March 2021-22 are estimated to be US 669.7 billion, witnessing a growth of 34.5 over the sameperiod last year and an increase of 27.2 over April to March 2019-20. India has been able to beat theoverall export target of US 650 billion despite the global economic slowdown caused by the Covid-19pandemic and the recent geopolitical developments in Europe. As the pandemic receded, Indiawitnessed a revival in domestic demand resulting in strong import growth. During the year 2021-22,India's overall imports (Merchandise and Services combined) are estimated to be US 756.7 billion,growing 47.8 over the same period last year and 25.5 over the year 2019-20, crossing the prepandemiclevel. China, UAE, and the USA were the largest import sources for India.